Purification, biochemical and functional characterization of miliin, a new thiol-dependent serine protease isolated from the latex of Euphorbia milii - Moro, L. P. [UNESP]; Murakami, M. T.; Cabral, H.; Vidotto, A.; Tajara, E. H.; Arni, R. K. [UNESP]; Juliano, L.; Bonilla-Rodriguez, G. O. [UNESP] (Bentham Science Publishers, 2008)
Miliin, a new thiol-dependent serine protease purified from the latex of Euphorbia milii possesses a molecular weight of 79 kDa, an isoelectric point of 4.3 and is optimally active at 60°C in the pH range of and 7.5-11.0. Activity tests indicate that milliin is a thiol-dependent serine protease. © 2008 Bentham Science Publishers Ltd.
Keywords: Characterization; Euphorbia milii; Latex; Medicinal plant; Purification; Serine protease